Analisis Kelayakan Investasi Pembangunan Tol Layang Jakarta-Cikampek (MBZ) Menggunakan Metode NPV, IRR, BCR, dan Payback Period - Adhit Trio Prayogi; Amri Gunasti (CV. Akira Java BUlu, 2026)
To address severe traffic bottlenecks and support the Trans-Java logistics corridor, the Sheikh Mohamed Bin Zayed (MBZ) Elevated Toll Road was established as a paramount national infrastructure. This research assesses the economic justification and financial viability of this IDR 16.2 trillion capital expenditure by deploying Net Present Value (NPV), Internal Rate of Return (IRR), Benefit Cost Ratio (BCR), and Payback Period (PBP) analyses. Utilizing a 40-year concession timeframe and the current integrated tariff of IDR 27,000 for Class I vehicles, the projected net annual cash flow reaches IDR 1.5 trillion. At a predetermined discount rate of 8%—reflecting the benchmark interest rate and macroeconomic risk premiums—the findings reveal an NPV of IDR 1.68 trillion, an IRR of 8.96%, a BCR of 1.10 (>1), and a return on investment duration (PBP) of 10.8 years. The extended discussion highlights that while the project is proven to be a highly lucrative long-term asset, mitigation of operational risks and inflation must remain a priority for the concession holder. Consequently, this elevated toll road is proven to be financially sound and commercially feasible.